Kinetic and Mechanism Studies Using Shrinking Core Model for Copper Leaching from Chalcopyrite in Methanesulfonic Acid with Hydrogen Peroxide. (2nd January 2021) - Wu, Jiajia; Ahn, Junmo; Lee, Jaeheon
ABSTRACT: An investigation on copper leaching from a chalcopyrite concentrate in methanesulfonic acid (MSA) and hydrogen peroxide at 75°C was carried out. Periodic additions of H2 O2 were applied to enhance chalcopyrite dissolution and the reaction mechanism was analyzed using a shrinking core model. The results revealed that compared with the addition of H2 O2 at the very beginning, periodic additions of H2 O2 enhanced copper extraction and leaching kinetics, and the rate-determining step shifted from the diffusion of oxidant to the surface chemical reaction. The reaction orders with respect to MSA and H2 O2 were found to be 0.19 and 1.26, respectively, suggesting the leaching process was highly dependent on H2 O2 concentration. Calculated activation energy between the temperature range of 25–75°C was 79.8 kJ/mol. Detailed study also indicated the reaction mechanism is diffusion-controlled through a protective sulfur layer at lower temperature and surface chemical reaction-controlled at temperatures higher than 55°C. Overall, the MSA–H2 O2 leaching system is a green method for chalcopyrite leaching and a possible flowsheet in the industrial application with the periodic additions of H2 O2 .